Meeting report: WHO consultation on accelerating Lassa fever vaccine development in endemic countries, Dakar, 10–11 September 2019. Issue 26 (27th May 2020) - Salami, Kolawole; Gsell, Pierre-Stéphane; Olayinka, Adebola; Maiga, Diadie; Formenty, Pierre; Smith, Peter G.; Moorthy, Vasee
Abstract: At the time of writing in 2019, there have been 754 confirmed cases of Lassa fever in Nigeria, 21% of whom have died. Lassa is on the priority pathogen list for WHO's R&D Blueprint for Action to Prevent Epidemics. In September 2019, WHO convened 67 scientists, regulators, ethicists, public health officials, funders and vaccine developers to discuss the end-to-end clinical development plan for Lassa fever vaccines. The substantial increases in vaccine trial capacity in Africa were reviewed, together with lessons learned from the evaluation of vaccines against HIV, TB, malaria, and Ebola in Africa. Participants agreed on a pathway for Lassa vaccine trial progression, as outlined in WHO's Lassa fever R&D roadmap and the WHO Lassa fever Target Product Profile. Two Phase 1 trials of Lassa vaccines have already started, and it was agreed that continuing interactions between high income and African regulatory and ethics authorities and WHO will be important in progression towards Phase 2b/3 efficacy trials in Lassa fever endemic areas. There was agreement that, for diseases whose burden is mainly in Africa, it should be the norm that African regulatory authorities are consulted on trial design/progression before first-in-human Phase 1 trials. Phase 2b-3 vaccine trial capacity needs to be in place in high Lassa fever burden areas where efficacy trials will take place. Licensure of one or more Lassa fever vaccines suitable for West African populations is a realistic goal in the next 5 years, with CEPI and WHO aligned on the pathway forward for vaccine development.